Adjuvant versus Neoadjuvant Immunotherapy for Hepatocellular Carcinoma: Clinical and Immunologic Perspectives - Su, Yung-Yeh; Li, Chia-Chen; Lin, Yih-Jyh; Hsu, Chiun (Seminars in Liver Disease, 2021)
Advancement in systemic therapy, particularly immune checkpoint inhibitor (ICI)-based combination regimens, has transformed the treatment landscape for patients with advanced hepatocellular carcinoma (HCC). The advancement in systemic therapy also provides new opportunities of reducing recurrence after curative therapy through adjuvant therapy or improving resectability through neoadjuvant therapy. Improved recurrence-free survival by adjuvant or neoadjuvant ICI-based therapy has been reported in other cancer types. In this article, developments of systemic therapy in adjuvant and neoadjuvant settings for HCC were reviewed. The design of adjuvant and neoadjuvant therapy using ICI-based regimens and potential challenges of trial conduct and result analysis was discussed. Results from these trials may extend the therapeutic benefit of ICI-based systemic therapy beyond the advanced-stage disease and lead to a new era of multidisciplinary management for HCC.
Keywords: antiangiogenic; biomarkers; cytotoxic T-lymphocyte-associated protein 4 (CTLA4); program cell death-1 (PD-1); tumor microenvironment